The Factors Affecting the Absorption of Ozone in Water - H. Sulaymon, Abbas; H. Al.Karaghouli, Abdul Razzak; Hassan Flayeh, Mustafa (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
This study was concerned with using ozone gas in drinking water treatment plant at Ibn-Sina Company. The main purpose of this research is to find the best contactor for ozone unit proposed. An investigation was conducted to study the absorption of ozone by water in two type of absorber. The effects of the process variables (such as height of water column, contact time, and pH) on the amount of ozone absorbed were investigated. Box-Wilson central composite rotatable design is used to design the experimental work for the mentioned variables. It was found that the optimum value of the variables studied was: i) Height of water column (90 cm) ii) Contact time (17-18 min) iii) PH (7 - 7.5)